Estimated acceptance of ovarian radiation absorbed dose in abdominal examination using the 10 kV rule method based on Caldose_X Software - Dian Nuramdiani; Surdiyah Asri Ningrum (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
Radiation exposure to the ovaries due to abdominal radiology is unavoidable given its location in the lower abdomen. Ovaries are organs that have a high level of sensitivity to radiation. One of the efforts used in the application of radiation protection optimization is the use of the 10 kV rule method. This study aimed to determine the estimated reception of ovarian radiation dose on abdominal radiology examination. The examination was carried out by anteroposterior (AP) projection of the female body phantom (FAX06) using Caldose_X software. The beam variation is set from 60kV/32mAs to 100kV/2mAs. The results of the ovarian radiation dose examination were: 0.484mGy for 60kV/32mAs, 0.402mGy for 70kV/16mAs, 0.309mGy for 80kV/8mAs, 0.227mGy for 90kV/4mAs, and 0.154mGy for 100kV/2mAs. When compared with the radiation dose limit for the abdominal examination set by BAPETEN, the data for this study were much smaller. Likewise, when compared with the reference results of previous studies, the data on ovarian radiation dose reception in this study were still within safe limits.